CD-34 negative solitary fibrous tumor of the prostate: A case report - Parker Heger; Austin Hill; Cameron Charchenko (Urology Case Reports)
Solitary fibrous tumor is an uncommon myofibroblastic tumor that affects pleura. While most of these tumors are in the intrathoracic cavity, a small minority have been noted to be found elsewhere, including the prostate. In this case study, we present a patient who presented with obstructive urinary symptoms and was diagnosed with solitary fibrous tumor of the prostate on immunohistochemical staining.